Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Financial Technology terhadap Kinerja Keuangan UMKM - Annisa Rahmawita; Nurul Jannah; Nurbaiti Nurbaiti (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study aims to analyze the influence of financial literacy, financial inclusion, and financial technology on the financial performance of MSMEs in Patumbak District, Deli Serdang Regency. The research approach used was an associative quantitative approach, with a sample of 100 MSMEs selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that, partially, financial literacy, financial inclusion, and financial technology have a positive and significant effect on MSME financial performance. Simultaneously, these three variables also significantly influence financial performance. These findings emphasize the importance of improving financial literacy, expanding access to formal financial services, and utilizing financial technology as strategic efforts to strengthen MSME business performance and sustainability. This research is expected to serve as an evaluation tool for MSMEs in improving financial management, expanding access to financial services, and encouraging the use of financial technology. It is also expected to provide input for the government and financial institutions in formulating MSME development strategies in Patumbak District.